2009
DOI: 10.1117/12.830225
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of mirror glass substrates for the NuSTAR mission

Abstract: The NuSTAR (Nuclear Spectroscopy Telescope Array) observatory (Harrison et al. 2009), expected to be launched into an equatorial low earth orbit in 2011, will have two mirror assemblies capable of imaging X-rays in the hard X-ray band between 5 keV and 80 keV. It will be the first X-ray observatory using multilayer coatings to significantly expand the bandwidth of the typical X-ray telescope of 0.1 keV to 10 keV. The mirror assemblies use a segmented design to simplify the construction process, as such they re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Over the last decade we have developed and perfected the slumping process [12,13,14,15,16,17,18,19,20,21,22,24] and successfully made thousands of 0.2 mm thick substrates [11] for the NuSTAR mission which was launched in June 2012 and has been in successful operation since. To date, we have been able to consistently make substrates with a figure quality between 4 and 8 arc-seconds HPD (two reflection equivalent), with the most probable (or average) value of 6 arc-seconds HPD.…”
Section: Substrate Fabricationmentioning
confidence: 99%
“…Over the last decade we have developed and perfected the slumping process [12,13,14,15,16,17,18,19,20,21,22,24] and successfully made thousands of 0.2 mm thick substrates [11] for the NuSTAR mission which was launched in June 2012 and has been in successful operation since. To date, we have been able to consistently make substrates with a figure quality between 4 and 8 arc-seconds HPD (two reflection equivalent), with the most probable (or average) value of 6 arc-seconds HPD.…”
Section: Substrate Fabricationmentioning
confidence: 99%
“…An advantage of this method is that the micro roughness of the mould does not affect the optical surface and is proven to be damped by almost a factor of 10 by the glass thickness. One could imagine the opposite scenario, and in fact this is being followed by some other groups [10,11]: the direct slumping uses a convex mould and the optical surface is in direct contact with the mould surface. This has the disadvantage that the micro roughness of the mould surface affects directly the optical surface of the mirror glass.…”
Section: A Glass Slumping Processmentioning
confidence: 99%
“…by NuSTAR [10], a NASA X-ray telescope launched in 2012, to be a technology well suited for X-ray telescope missions.…”
Section: A Segmented Mirror Modulesmentioning
confidence: 99%
“…This process, known as slumping, will cause the substrate to take the curvature of the mold (without sacrificing the optically smooth surface finish of the original wafer). It was used for the mirrors of the NuSTAR x-ray telescope [37]. It has been demonstrated that under carefully controlled conditions silicon can be slumped as well, at around 900°C [38].…”
Section: Curved Mirrorsmentioning
confidence: 99%